The Bonding and Reactivity of α-Carbonyl Cyclopropanes - Craig, Alexander J.; Hawkins, Bill C. (Synthesis, 2020)
The cyclopropane functionality has been exploited in a myriad of settings that range from total synthesis and methodological chemistry, to medical and materials science. While it has been seen in such a breadth of settings, the typical view of the cyclopropane moiety is that its reactivity is derived primarily from the release of ring strain. While this simplified view is a useful shorthand, it ignores the specific nature of cyclopropyl molecular orbitals. This review aims to present the different facets of cyclopropane bonding by examining the main models that have been used to explain the reactivity of the functionality over the years. However, even with advanced theory, being able to precisely predict the reactivity of an exact system is nigh impossible. Specifically chosen, carbonyl-bearing cyclopropyl species act as so-called acceptor cyclopropanes and, if correctly derivatised, donor–acceptor cyclopropanes. By undertaking a case study of the history of carbonyl cyclopropanes in organic synthesis, this review highlights the relationship between the understanding of theory and pattern recognition in developing new synthetic methods and showcases those successful in balancing this critical junction.1 Cyclopropanes2 The Strain Model3 The Forster–Coulsin–Moffit Model4 The Walsh Model5 Acceptor, Donor, and Donor–Acceptor Cyclopropanes6 Reactions of Carbonyl Cyclopropanes
Keywords: cyclopropanes; bonding; donor–acceptor cyclopropanes; homo-Michael additions; 1,3-dipolar cycloadditions